2018
DOI: 10.2224/sbp.6406
|View full text |Cite
|
Sign up to set email alerts
|

The impact of teen magazines on adolescent girls in North Cyprus

Abstract: This empirical study aims to investigate the image of beauty standards constructed by the Turkish teen magazines and its relation with the beauty understanding of Turkish Cypriot teenagers. Other issues investigated are the consumption behavior of teenagers who read teen magazines and the body satisfaction of teenage girls. This study employs three different methodologies. Firstly, a content analysis covering 12 issues each spanning 4 years is performed on two popular Turkish teen magazines, Hey Girl and Cosmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(74 reference statements)
2
2
0
Order By: Relevance
“…In line with this nding, previous studies also indicated a gender difference pattern regarding body features that are emphasized by adolescent boys and girls [23]. Furthermore, current study found that some features such as big eyes, colored eyes, straight white teeth, plump lips, a small and upturned nose, smooth and bright skin, thick and long hair, and long eyelashes were perceived as desirable traits by participants, which is similar to previous studies [29,31]. While most of the current study participants had dark-colored eyes and hair, having blue/green eyes, blond hair and an upturned nose were desired by them, which are more commonly idealized body features in Western societies [32].…”
Section: Discussionsupporting
confidence: 91%
“…In line with this nding, previous studies also indicated a gender difference pattern regarding body features that are emphasized by adolescent boys and girls [23]. Furthermore, current study found that some features such as big eyes, colored eyes, straight white teeth, plump lips, a small and upturned nose, smooth and bright skin, thick and long hair, and long eyelashes were perceived as desirable traits by participants, which is similar to previous studies [29,31]. While most of the current study participants had dark-colored eyes and hair, having blue/green eyes, blond hair and an upturned nose were desired by them, which are more commonly idealized body features in Western societies [32].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, current study found that some features such as big eyes, colored eyes, straight white teeth, plump lips, a small and upturned nose, smooth and bright skin, thick and long hair, and long eyelashes were perceived as desirable traits by participants, which is similar to previous studies [44,55]. While most of the current study participants had dark-colored eyes and hair, having blue/green eyes, blond hair and an upturned nose were desired by them, which are more commonly idealized body features in Western societies [56].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to athletes, the behaviour of artists published in various media is often an idol for teenagers. Yonca Aybay, a senior lecturer at Eastern Mediterranean Turkey University, said, "Girls' magazines, a media which is popular among young girls, are no exception to this, and teenagers are being targeted by a "consumer culture" idol with new fashion styles and look promoted by these magazines" (Yonca Aybay, 2016;Aybay & Kara, 2018). In Indonesia, an online media site kapanlagi.com has held a poll of the most fanatical and militant fans, followed by 92,694 votes.…”
Section: Introductionmentioning
confidence: 99%